Fine Structure of Microseismic Glacial Stick‐Slip. Issue 22 (18th November 2021) - Gräff, Dominik; Köpfli, Manuela; Lipovsky, Bradley Paul; Selvadurai, Paul Antony; Farinotti, Daniel; Walter, Fabian
Abstract: Frictional instabilities exist in many geological settings, including glaciers and tectonic plate boundaries. However, investigations of suggested analogies between stick‐slip "icequakes" and earthquake faulting have been hampered by the noisy, melt‐prone and inaccessible nature of glacial environments. Here, we reveal details of stick‐slip events beneath an Alpine glacier using seismic sensors within a few meters of a seismically active bed region. We present evidence that widely detected stick‐slip events, which are measurable at the ice surface, are in fact dynamic ruptures over many smaller asperities, whose individual seismic failures are usually too small to be recorded at the surface. Characteristic recurrence times of such multi‐asperity ruptures and their sizes suggest an analogy to Parkfield earthquakes on the San Andreas Fault, questioning traditional glacier sliding theories. Although several trillion times smaller, glacial seismic sources presented here may therefore be ideal for studying earthquake faulting due to much higher event rates. Plain Language Summary: Glaciers mostly move smoothly and slowly. But regularly at specific locations at the glacier bed, the ice suddenly slips forward. This slip causes an "icequake" which is similar to a small earthquake, but so weak, that one cannot feel it. However, electronic sensors on the ice surface can measure it but lots of information gets lost on the way to the sensor. For this reason, we drilled through two hundred meters of glacier ice to be as close as possible to such an icequake, and to capture all its details. We see that more tiny icequakes which are undetectable at the ice surface happen frequently and are distributed over an area corresponding to a badminton court. About every hour, there is an icequake 50 times stronger affecting all of this area. This behavior is similar to what was found at the San Andreas Fault in California. Specifically at the Parkfield section of the fault, where tiny earthquakes happen every day, but where every 25 years or so a big earthquake shakes the region. This similarity, and that icequakes under glaciers happen much more often, make glaciers to an ideal natural laboratory to study how big earthquakes form. Key Points: We study frictional processes at the bed of a glacier by drilling through 200 m ice and reaching an active stick‐slip asperity Seismicity that is not measurable from the ice surface clusters at distinct asperities located within a confined bed region Asperities host characteristic multi‐asperity ruptures, similar to the Parkfield section of the San Andreas Fault